C++ concurrency in action - Williams, Anthony (Software engineer) (Manning Publications, 2019)
"This book should be on every C++ programmer's desk. It's clear, concise, and valuable." Rob Green, Bowling Green State University This bestseller has been updated and revised to cover all the latest changes to C++ 14 and 17! C++ Concurrency in Action, Second Edition teaches you everything you need to write robust and elegant multithreaded applications in C++17. You choose C++ when your applications need to run fast. Well-designed concurrency makes them go even faster. C++ 17 delivers strong support for the multithreaded, multiprocessor programming required for fast graphic processing, machine learning, and other performance-sensitive tasks. This exceptional book/course unpacks the features, patterns, and best practices of production-grade C++ concurrency. C++ Concurrency in Action, Second Edition is the definitive guide to writing elegant multithreaded applications in C++. Updated for C++ 17, it carefully addresses every aspect of concurrent development, from starting new threads to designing fully functional multithreaded algorithms and data structures. Concurrency master Anthony Williams presents examples and practical tasks in every chapter, including insights that will delight even the most experienced developer. Inside: Full coverage of new C++ 17 features Starting and managing threads Synchronizing concurrent operations Designing concurrent code Debugging multithreaded applications This book/course is written for intermediate C and C++ developers. No prior experience with concurrency required. Anthony Williams has been an active member of the BSI C++ Panel since 2001 and is the developer of the just::thread Pro extensions to the C++ 11 thread library. A thorough presentation of C++ concurrency capabilities. Maurizio Tomasi, University of Milan Highly recommended for programmers who want to further their knowledge of the latest C++ standard. Frédéric Flayol, 4Pro Web C++ The guide contains snippets for everyday use in your own projects and to help take your concurrency C++ skills from the Padawan to the Jedi level. Jura Shikin, IVI Technologies NARRATED BY LISA FARINA AND DIANA GARDINER.